Historical peculiarities of formation of small town of Shebekino structure - Margarita Perkova; Anastasiia Zaikina (Architecture and Engineering, 2016)
The article is dedicated to study of historical peculiarities which influenced the social and economic development and formation of the functional and planning structure of the small town of Shebekino of the Belgorod Region. Time scheme of land owners based on historical documentary data and scheme of territorial development during period from the 19th till 21st centuries were developed. Development of the town-forming base under rule of the town of Shebekino by the Rehbenders is considered and logical interrelation of husbandries located within their possessions is made. Main historical and extant architectural monuments of that time, their placement in the town structure were analyzed to preserve historical and cultural development and steady continuity and harmony in development of the territories.